JAVANESE GRAMMATICAL STRUCTURE IN TRANSLATION OF SERAT ALPATÉKAH MANUSCRIPT - Febriyanti, Fitri (Academic Journal of Islamic Principles and Philosophy, 2024)
The Qur'an is translated and interpreted using Javanese to spread Islam in Java. A handwritten Javanese script called Serat Alpatékah is used. The Javanese language's structure and Islamic history have never been combined to analyze this manuscript. Descriptive-philological research is the methodology employed. This type of research combines descriptive and philological methods. Words, phrases, and sentences (part of grammatical structure) from Surah Al-Fatihah and Al-Baqarah in Serat Alpatékah manuscript were used as the research's primary sources of information. The study's findings indicate that 1) Rekso Pustoko Puro Mangkunegaran Office, Surakarta owns the Serat Alpatékah manuscript used for script teaching. The script's purported author is R.Ng. Ronggowarsito. Using conventional techniques, text from manuscripts made of Serat Alpatékah is transliterated. The form of the text critique apparatus in the text is adjusted according to the Javanese dictionary. Standard techniques for text editing in the manuscript Serat Alpatékah. Eugene A. Nida's translation theory is applied to ascertain the sentence structure found in Javanese, the target language; 2) The analysis phase explains the textual, contextual, and grammatical relationships. The Javanese sentence structure revealed in the Serat Alpatékah manuscript is related to the tafsiriyah translation process. The aim of translation is to convey the message from the source language to the target language. To achieve this goal, the Serat Alpatékah manuscript is never translated without grammatical analysis or text restructuring.